2020
DOI: 10.1136/bcr-2020-234962
|View full text |Cite
|
Sign up to set email alerts
|

Agenesis of the long head of the biceps brachii tendon: ignored variations of the anatomy and the next tendon to disappear?

Abstract: Bilateral agenesis of the long head of the biceps brachial tendon (LHB) is a very rare variation of the anatomy. We report a case of an 18-year-old man with bilateral agenesis of the long head of the biceps brachii tendon. We present initial findings, radiographical examinations and the follow-up of an unusual entity. Diagnosis of agenesis of the LHB can be challenging especially in cases of traumatic shoulder pain. It is not a very known entity because of its rareness. However, it could be associated with oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…According to major studies, the incidence rate of shoulder deformity increases after LHBT tenotomy compared to that after tenodesis. [ 22 - 24 ] In a recent retrospective study by Godenèche et al,[ 25 ] during the 10-year follow-up, no deformity occurred at all after LHBT tenodesis or tenotomy. A total of 11.4% of patients undergoing tenodesis suffer from Popeye deformity, possibly as the biceps tendon has insufficient tension or the tendon is in a position where the biceps tendon is over-relaxed.…”
Section: Discussionmentioning
confidence: 99%
“…According to major studies, the incidence rate of shoulder deformity increases after LHBT tenotomy compared to that after tenodesis. [ 22 - 24 ] In a recent retrospective study by Godenèche et al,[ 25 ] during the 10-year follow-up, no deformity occurred at all after LHBT tenodesis or tenotomy. A total of 11.4% of patients undergoing tenodesis suffer from Popeye deformity, possibly as the biceps tendon has insufficient tension or the tendon is in a position where the biceps tendon is over-relaxed.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical variations of LHBT, affecting approximately 6–10% of the studied population ( 8 ), typically encompass aberrant tendon origin, supernumerary accessory heads, intra-articular tendon mobility, and tendon absence. The association between these variations and patient-related shoulder manifestations such as instability, pain, or diminished shoulder function is rather uncertain due to the predominance of case studies in current literature ( 9 , 10 ). There is only one study with a larger population that identified a correlation between proximal LHBT tendon anatomical variations (sublabral foramen, cord-like middle glenohumeral ligament, or Buford complex) and an increase in passive internal rotation at a 90° abduction ( P = 0.046), leading to anterosuperior labral fraying ( P = 0.000) ( 11 ).…”
Section: Lhbt’s Role In Shouldermentioning
confidence: 99%